Physicochemical Fruit-harvest Indicators for Haden, Kent, Palmer, and Keitt Mango (Mangifera indica L.) Varieties Cultivated in Ghana for Export and Local Markets - Abu, Moomin; Abbey, Lawrence Dzarkwei; Amey, Nelson Kobla (Current Research Progress in Agricultural Sciences Vol. 5, 2024)
Background: Most mango (Mangifera indica L.) varieties grown in Ghana for export include Haden, Kent, Palmer, and Keitt; all of Florida origin and have different post-harvest characteristics. The issue of few exportable mango fruits in Ghana can be attributed to inappropriate post-harvest handling and the inability of farmers to determine the appropriate time of fruit maturity; all of which are significant contributors to poor-quality fruit. Purpose: Field and laboratory studies were conducted at Prudent Export and Import Company Ltd Mango Plantation and at the Bio-chemistry Laboratory of Food Research Institute, Legon, Accra, Ghana, respectively. For field studies, fruit ages (early, mid, and late harvest stages) of Haden, Kent, Palmer, and Keitt mango varieties were determined through ‘age-control’ and established for physiological (early harvest) and eat-ripeness stages (mid and late harvests). This was followed by laboratory studies to determine the physicochemical properties at these physiological and eat-ripeness stages that could be used as simple harvest indicators for export and local markets. Research Methods: Randomized Complete Block Design and Completely Randomized Design with four replications in each case were used for field and laboratory studies respectively. For each of the four varieties, five mango trees were sampled at random in each of the four replications of Prudent Export and Import Company Ltd Mango Plantation in the Greater Accra region of Ghana, to accomplish the purpose of the study. Findings: Established harvest stages (ages) at physiological maturity/early harvest, mid-harvest, and late harvest for Haden were 112, 119, and 126 days from fruit-set, respectively; for Kent 126, 133, and 140 days from fruit-set, respectively; for Palmer 133, 140, and 147 days from fruit-set, respectively; and for Keitt 140, 147, and 154 days from fruit-set, respectively. Established TA (% citric acid), Ascorbic acid (mg.100g-1), TSS (oBrix), pH, Moisture (%), DM (%), Fibre (%), and TSS/Acidity ratio readings at physiological maturity for Haden were 1.071, 24.90, 8.94, 3.250, 83.55, 16.45, 0.017, and 8.3473 respectively; for Kent 0.807, 8.50, 6.88, 3.499, 82.28, 17.72, 0.016, and 8.5254 respectively; for Palmer 0.940, 35.50, 7.25, 3.328, 83.89, 16.11, 0.017, and 7.7128 respectively; and for Keitt 1.004, 23.80, 6.56, 3.349, 84.26, 15.74, 0.026, and 6.2835 respectively. Established TA (% citric acid), Ascorbic acid (mg.100g-1), TSS (oBrix), pH, Moisture (%), DM (%), Fibre (%), and TSS/Acidity ratio readings at eat-ripe maturity for Haden were 0.14, 8.05, 18.50, 5.11, 80.85, 19.15, 0.065, and 132.140 respectively; for Kent 0.12, 3.32, 17.50, 4.08, 80.94, 19.06, 0.062, and 145.830 respectively; for Palmer 0.31, 5.52, 19.10, 5.00, 80.25, 19.75, 0.066, and 61.610 respectively; and for Keitt 0.10, 3.66, 17.00, 5.80, 81.95, 18.05, 0.094, and 170.00 respectively. Pulp colour (turning yellow) was nearly the same for the different varieties at physiological maturity but varied when ripe, with uniform consistent texture at both stages. TA, Ascorbic Acid, TSS, pH, Moisture, DM, Fibre, Pulp/flesh Colour, Pulp Consistency, and TSS/Acidity ratio have all been established as physicochemical indices that could be used as harvest indicators at both physiological and eat-ripe stages for Haden, Kent, Palmer, and Keitt mango varieties cultivated in Ghana for export and local markets. Limitations: No limitations to report. Originality/Value: Fruit should be harvested after full maturity in order to develop the most adequate organoleptic quality and the longest post-harvest life, and before full ripeness but should never be over-ripe or immature for any purpose unless otherwise.